Photoinduced Processes within Noncovalent Complexes Involved in Molecular Recognition. Issue 10 (4th February 2020) - Abdelmouleh, Marwa; Lalande, Mathieu; Vizcaino, Violaine; Schlathölter, Thomas; Poully, Jean‐Christophe
Abstract: Investigating the intrinsic properties of molecular complexes is crucial for understanding the influence of noncovalent interactions on fundamental chemical reactions. Moreover, specific molecular recognition between a ligand and its receptor is a highly important biological process, but little is known about the effects of ionizing radiation on ligand–receptor complexes. The processes triggered by VUV photoabsorption on isolated noncovalent complexes between the glycopeptide antibiotic vancomycin and a mimic of its receptor have been probed by means of mass spectrometry and synchrotron radiation. In the case of protonated species, the glycosidic bond of vancomycin was cleaved with low activation energy, regardless of the molecular environment. In sharp contrast, for deprotonated species, electron photodetachment from carboxylate groups only triggered CO2 loss, whereas the glycosidic bond remained intact. Importantly, the noncovalent complex was also found to survive VUV photoabsorption only when the native structure is conserved in the gas phase. Abstract : Induced by light : Electron removal induced by VUV photoabsorption was found to trigger facile glycosidic bond cleavage within a protonated antibiotic–receptor complex in the gas phase. In sharp contrast, the corresponding deprotonated complex, which retains its native structure when isolated, partly survives and mostly loses CO2 .